Influence of Supply Chain Management on Universities Development: An Outward Glance - Gabdrakhmanov, Niyaz K; Abilov, Albert V; Vershinina, Olga A; Novenkova, Aida Z; Medvedeva, Marina Yu (ExcelingTech, 2019)
This study is devoted to assessing the supply chain management impact on universities promotion and efficiency in international and Russian universities' ratings on their development. The peculiarity of the study is that it considers both universities participating in the competitive recovery program and presented in international rankings, as well as those that do not participate therein. The paper analyzes the rating indicators, the development strategy and the positioning of four Russian universities: Kazan (Volga Region) Federal University (KFU), National Research University